Diversity of Alternaria Section Nimbya in Iran, with the Description of Eight New Species - Abdollah Ahmadpour; Youbert Ghosta; Zahra Alavi; Fatemeh Alavi; Alireza Poursafar; Pabulo Henrique Rampelotto (Journal of Fungi)
Alternaria includes endophytes, saprophytes, and pathogens affecting both plants and animals, with a global distribution across various hosts and substrates. It is categorized into 29 sections, each defined by a type species and six monophyletic lineages. The Alternaria section Nimbya comprises 10 species primarily associated with the families Juncaceae and Cyperaceae, functioning as either saprophytes or plant pathogens. In this study, 189 fungal strains were collected from multiple locations across six provinces in Iran. The isolates were initially classified based on morphological characteristics and ISSR-PCR molecular marker banding patterns. Multi-gene phylogenetic analyses of 38 selected strains, using ITS–rDNA, GAPDH, TEF1, RPB2, and Alt a 1 gene sequences, combined with morphological data, led to the identification of 13 species, including eight new species, namely Alternaria caricifolia, A. cyperi, A. juncigena, A. junci-inflexi, A. persica, A. schoenoplecti, A. salkadehensis, and A. urmiana. In addition, this work identified new host associations (matrix nova) for three previously known species: A. caricicola on Cyperus sp., A. cypericola on Eleocharis sp., and A. junci-acuti on Carex sp. The study provides detailed morphological descriptions and illustrations of all identified species, discusses their habitats, distribution, and phylogenetic relationships within section Nimbya, and presents a key for species identification within this section in Iran. Furthermore, these findings highlight the significance of studying fungal biodiversity in Iran and contribute to a better understanding of species distribution and host range within the Alternaria section Nimbya.